CORRELATION OF THE MORPHOLOGICAL CHARACTERISTICS AND SPORTS ACHIEVEMENTS IN KARATE - Duško Bjelica; Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Karate is characterized by the dynamics of movements, which is especially pointed out through the actions of attack and defense, while the static situation during the match is almost nonexistent. Many characteristic movements, primarily strokes that are strictly defined technical way of performance, are performed at maximum speed and precision. Only if made in the foregoing, the judges scored them, which results in the victory of one of the karate players. Karate is different from other martial arts because of the duration of the fight. Karate fight lasts three minutes of pure battle (two minutes for women) and is interrupted by frequent interruptions, which is sufficient for the trained fighters for the relative recovery.